2014
DOI: 10.1016/j.jalz.2014.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Dependence in Alzheimer's disease and service use costs, quality of life, and caregiver burden: The DADE study

Abstract: The construct of dependence may help to translate the combined impact of changes in cognition, function, and behavior into a more readily interpretable form. The DS is useful for assessing patients with AD in clinical trials/research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
49
0
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(55 citation statements)
references
References 34 publications
2
49
0
4
Order By: Relevance
“…This can be done from cross-sectional data, for example, by estimating mean outcomes in each relevant disease state or by estimating statistical functions with each outcome as the dependent variable and the intermediate outcomes as explanatory variables. The dependence scale, which measures the patient's care need, has been suggested to be a valuable tool to bridge between patients' abilities to perform activities of daily living and what care is actually provided to them [48].…”
Section: Consensus On Choice Of Relevant Outcomes Is Missingmentioning
confidence: 99%
“…This can be done from cross-sectional data, for example, by estimating mean outcomes in each relevant disease state or by estimating statistical functions with each outcome as the dependent variable and the intermediate outcomes as explanatory variables. The dependence scale, which measures the patient's care need, has been suggested to be a valuable tool to bridge between patients' abilities to perform activities of daily living and what care is actually provided to them [48].…”
Section: Consensus On Choice Of Relevant Outcomes Is Missingmentioning
confidence: 99%
“…Therefore, estimates evaluating AD as the 3rd most frequent cause of death in US [7], and possibly in the other developed countries with a long life expectancy are likely to be more realistic. Moreover, health care costs related to dementias (that is, mostly to AD) are estimated at the level of $259 billion in the year 2016 [6], and AD is one of the major factors affecting the quality of life at an advanced age [8]. In case of TSEs, the epidemics of "mad cow" disease led to huge losses in the European cattle industry [5].…”
Section: Introductionmentioning
confidence: 99%
“…1014 Previous research has shown that dependence directly impacts costs of care and is associated with HRQoL and caregiver burden. 7,9,12,15 Studies have also suggested that the DS is a better candidate than the MMSE or CDR for modeling AD progression and in explaining variation in quality of life, health status and medical costs of AD patients, as well as caregiver time and associated resource use. 5,9,16 These studies suggest that the DS would be useful in models evaluating the economic impact of interventions in AD.…”
Section: Introductionmentioning
confidence: 99%